Maternal obesity and the impact of associated early-life inflammation on long-term health of offspring - Denizli, Merve; Capitano, Maegan L.; Kua, Kok Lim (Frontiers in Cellular and Infection Microbiology, 2022)
The prevalence of obesity is increasingly common in the United States, with ~25% of women of reproductive age being overweight or obese. Metaflammation, a chronic low grade inflammatory state caused by altered metabolism, is often present in pregnancies complicated by obesity. As a result, the fetuses of mothers who are obese are exposed to an in-utero environment that has altered nutrients and cytokines. Notably, both human and preclinical studies have shown that children born to mothers with obesity have higher risks of developing chronic illnesses affecting various organ systems. In this review, the authors sought to present the role of cytokines and inflammation during healthy pregnancy and determine how maternal obesity changes the inflammatory landscape of the mother, leading to fetal reprogramming. Next, the negative long-term impact on offspring’s health in numerous disease contexts, including offspring’s risk of developing neuropsychiatric disorders (autism, attention deficit and hyperactive disorder), metabolic diseases (obesity, type 2 diabetes), atopy, and malignancies will be discussed along with the potential of altered immune/inflammatory status in offspring as a contributor of these diseases. Finally, the authors will list critical knowledge gaps in the field of developmental programming of health and diseases in the context of offspring of mothers with obesity, particularly the understudied role of hematopoietic stem and progenitor cells.